Proposta conceitual de zoneamento ambiental para o Município de Erechim (RS) - Rampazzo, Sônia Elisete (2003)
This work proposed an environmental zoning based on the potencialities and fragilities of the use of the land. Its perspective was to subsidize the elaboration of proposals and lines of direction for the re-ordering of the landscape of the municipality of Erechim, contributing to local-regional development. The town is a part of the Geographic Micro-region of Erechim, inserted phisiographically in a portion of Brazil s Southern Plateau in the center of Rio Grande do Sul State. Based on the understanding that spatial order can be an instrument of environmental policy, the landscape was studied through overlapping techniques of thematic maps, aiming to promote the protection of the environment, the presevation of its quality and sustainable usage of its natural resources. The production and analysis of the maps was performed using Geopraphic Information Systems, LANDSAT satelite images and aerial photographs and a cartographic basis. The obtained analysis (mapping of phisycal environment) was subsidized by intensive field work, trying to represent the dynamics and functioning of each portion (units of landscape analysis). The environmental analysis of the area of study consisted in: characterizing the area of study acording to its environmental compartments; analyzing the diferents uses of the land; determining and characterizing the units of landscape analysis; elaborating a proposal for the handding of the landscape (environmental zoning). It was possible to propose actions for reduction of environmental degradation and protection of local-regional biodiversity from the synthesis of these analysis. Although one is aware that the work must be continued, this research represents a first step towards the elaboration of proposals and lines of direction for the space re-ordering of landscape within the concep of environmental planning.